Peutz-Jeghers syndrome with gastric-type mucinous endocervical adenocarcinoma and sex-cord tumor with annular tubules: A case report - Li, Xuanyan; Qi, Yue; Zhang, Wenwen; Rao, Yang; Zhang, Na; Qu, Pengpeng (Frontiers in Medicine, 2023)
Peutz-Jeghers syndrome(PJS) is a rare autosomal dominant genetic disorder characterized by mucocutaneous pigmentation and multiple hamartomatous polyps in the gastrointestinal tracts. About 11% of female PJS patients are diagnosed with Gastric-type endocervical adenocarcinoma(G-EAC) and about one third have a sex-cord tumor with annular tubules(SCTATs). Gastric-type endocervical adenocarcinoma is a special subtype of cervical adenocarcinoma which accounts for only 1%-3%. Here we report a rare case of a 31-year-old woman affected with G-EAC and SCTAT accompanied by PJS. After surgery, we followed up for 5 years without recurrence.